Course on soft ground tunnelling 20-22 September 1988 (Thomas Telford, 1988)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a course held in September 1988.
Keywords: Tunneling -- Congresses.; Soil mechanics -- Congresses.; Underground construction -- Congresses.; elektronické knihy; electronic books